Allometric height-diameter equations for Pinus pseudostrobus Lindl - Hernandez Ramos, Jonathan; García Magaña, J. Jesús; Hernández Ramos, Adrián; García Cuevas, Xavier; García Espinoza, Guadalupe Geraldine; Muñoz Flores, Hipolito Jesús; Sáenz Reyes, José Trinidad (Ecosistemas y Recursos Agropecuarios, 2018)
Silvicultural practices used for forest management in the Indigenous Community of Nuevo San Juan Parangaricutiro (CINSJP for its initials in Spanish), Michoacan, Mexico, are important for the sustainability of its woodlands. For this purpose, techniques that provide reliable and current quantitative estimates are required. The aim was to t an equation that describes the allometric relationship between total height and normal diameter (Th-nd) of Pinus pseudostrobus in the CINJSP forests. Data were obtained from P. pseudostrobus stands that have been managed with the Silvicultural Development Method (SDM) at di erent stages according to the current forest management program. The research area is between 2,200 and 2 500 masl, has a temperate type C (w2) climate, and is located at southwest of the Purhépecha Plateau within the Trans-Mexican Volcanic Belt region. The sample size consisted of 169 total height-normal diameter (Th-nd) data pairs. Ten allometric models to evaluate the goodness of t were tested, choosing three models based on the lowest values of the sum of square errors of prediction (SSE) and the root mean squared error (RMSE), the highest adjusted coe cients of determination and the signi cance of their parameters. The deviations of the models were smaller than 0.01 m. The three-parameter equation T h = K + 38.06004/1+6.033101exp(0.066439dn) proved to be statistically more stable than the rest, and it also shows deviations of less than one meter per tree and less than 1% for the entire population.